ASDモデルマウスの社会性行動と前頭前皮質の機能異常 - 中井, 悠花; 彌永, 祐輔; 早田, 敦子; 林田, 美鈴; 橋本, 均; 原, 雄大; 大久保, 仁; 山口, 瞬; 田沼, 将人; 田熊, 一敞; 横山, 玲; 吾郷, 由希夫; et al. (日本薬理学会年会要旨集, 2022)
Unapproved use of some antiepileptic drugs has been reported to ameliorate core social deficits of autism spectrum disorder (ASD); however, the neural mechanisms remain unclear. Here, using brain-wide neuronal activation mapping in Arc-dVenus reporter mice, we showed that ASD model mice exhibited not only aberrant hyperactivation in multiple brain areas during social interaction but also disruption of prefrontal nodes in the brain network associated with social impairments. Three unapproved-use drugs for core ASD symptoms reversed the social deficits and dysfunction of the prefrontal nodes in the brain network. In addition, we identified a new unapproved use drug that reversed the social deficits and the dysfunction of prefrontal nodes during social interactions in ASD mice. These results suggest that prefrontal nodes in the brain network can be a diagnostic feature and a therapeutic target for the core symptoms of ASD and that its monitoring is useful to predict the therapeutic effect of ASD drug candidates.